DDIS-20. IMIPRIDONE STRUCTURE ACTIVITY RELATIONSHIP UNCOVERS ONC206 AS THE NEXT BITOPIC DRD2 ANTAGONIST FOR ONCOLOGY WITH DIFFERENTIATED RECEPTOR PHARMACOLOGY. (11th November 2019) - Prabhu, Varun; Cuoco, Caroline; Jung, Jinkyu; Rahman Kawakibi, Abed; Willette, Blair; Day, Marilyn; Anantharaman, Lakshmi; Charter, Neil; Rucker, Joseph; Doranz, Benjamin; Oster, Wolfgang; Stogniew, Martin; et al.
Abstract: ONC201 is the first bitopic antagonist of dopamine receptor D2 (DRD2) in oncology clinical trials, which have shown that the small molecule is well tolerated and induces durable tumor regressions in H3 K27M-mutant glioma patients. ONC201 possesses a unique tri-heterocyclic core structure that prompted a medicinal chemistry exploration following its successful clinical translation. Chemical derivatization of the ONC201 pharmacophore from an angular to a linear isomer ablated DRD2 antagonist activity and anti-cancer activity, indicating the core structure integrity is critical. A series of analogs that share the same core structure, called imipridones, were profiled for modulation of β-arrestin recruitment to GPCRs and anti-cancer efficacy. The profiled imipridones exhibited a heterogeneous spectrum of GPCR agonist/antagonist activity that was exclusive to Class A GPCRs. The addition of electron withdrawing groups to one of two peripheral benzyl rings enhanced the potency of GPCR engagement and anti-cancer effects, while derivatization of the other benzyl ring was inactivating. Among the GPCR hits identified, maximal variance in imipridone GPCR antagonism was identified for DRD2/DRD3. ONC206 emerged as the most selective and potent antagonist for DRD2/DRD3 with a Ki of ~320nM for DRD2 with complete specificity across human GPCRs and complete DRD2 antagonism. Schild analyses of ONC206 in cAMP and β-Arrestin recruitment assays revealed hallmarks of non-competitive DRD2 antagonism, unlike antipsychotics but similar to ONC201. Shotgun mutagenesis across DRD2 identified 7 residues critical for ONC206-mediated antagonism at orthosteric and allosteric sites. Six residues were critical for ONC201 and ONC206, however the impact varied between the two compounds and one allosteric residue was exclusive to ONC206. Structural mapping revealed that some ONC206-critical allosteric residue interactions are located at the interface of TM-IV and –V that mediates the DRD2 homodimer interface. Thus, ONC206 is a bitopic DRD2 antagonist that may be poised to address oncogenic DRD2 monomers or dimers.